Browsing Spatial Knowledge with Linked Ontologies - Reed, Tristan; Reitsma, F.; McMeekin, David (IEEE, 2015)
Browsing spatial knowledge using linked ontologies supports multiple views on spatial data and allows users to explore that data with concept browsing or spatial feature browsing which are linked. A prototype application, KnowledgeScape, has been developed to demonstrate said data exploration.